Conceptual Terminological Structure of Pedagogy as the Subject of Historical Pedagogic Research - Y. A. Koshkina (Russian State Vocational Pedagogical University, 2015)
The paper is devoted to the formation and development of pedagogic terminology. The author theoretically substantiates the potential of the historical pedagogic research concerning the conceptual and terminological structure of the Russian pedagogy. The research is based on the following ideas: correlation between the scientific terminology formation and scientific knowledge genesis; philosophic concept as a form and result of reality reflection; linguistic concept of the term as a functional unit of a scientific language; specifics of pedagogic knowledge reflection in conceptual form. The main research findings include identifying methodological requirements for analyzing the conceptual scientific formation in historical context; substantiating the resource basis; revealing the investigation principles; describing the tools and their implementation peculiarities with regard to the specifics of pedagogical concepts and terms. The acquired results can be used while exploring the pedagogic history problems, pedagogic methodology and terminology. In conclusion, the actual research trends of pedagogic terminology formation are reviewed from the historical pedagogic perspective.